Trinity Cathedral, T'dad. - (:unkn) unknown (My University, 2010)
Image depicts a view of the Trinity Cathedral, located in the capital city of Port of Spain, on the island of Trinidad in the twin-island Republic of Trinidad and Tobago. This angular view of the cathedral is from the north western end of Hart Street looking in a south easterly direction.
Colour: Sepia; Style: Portrait; Other: Unbordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings; Port of Spain